Treatment with angiotensin receptor neprilysin inhibitor for Taiwan heart failure patients: Rationale and baseline characteristics of the TAROT-HF study. Issue 9 (7th July 2021) - Lin, Wen-Yu; Chung, Fa-Po; Liao, Chia-Te; Huang, Jin-Long; Liang, Huai-Wen; Lee, Ying-Hsiang; Lin, Po-Lin; Chiou, Wei-Ru; Hsu, Chien-Yi; Chang, Hung-Yu
Abstract : Background: This study used a real-world database to investigate the prescription patterns of sacubitril/valsartan (Sac/Val) among Taiwanese patients with heart failure with reduced ejection fraction (HFrEF). Methods: The Treatment with Angiotensin Receptor neprilysin inhibitor fOr Taiwan Heart Failure patients (TAROT-HF) study is a principal investigator–initiated, multicenter, observational, retrospective study on Taiwanese HFrEF patients. A total of 1772 patients with HFrEF (mean age 62.5 years, 75.3% male, mean left ventricular ejection fraction [LVEF] 29.3%) who received Sac/Val at 10 hospitals between 2017 and 2018 were enrolled at the date of Sac/Val initiation. Among these patients, 585 (33%) initially received Sac/Val during acute decompensated heart failure (HF) hospitalization (TAROT-AHF arm), whereas 1187 (67%) initially received the same at the outpatient clinic (TAROT-CHF arm). Results: A total of 1343 (75.8%) patients received an initial dose of 50 mg twice daily or fewer, whereas 422 (23.8%) received the standard initiation dose (100 mg twice daily). During outpatient Sac/Val initiation, the mean dosages were significantly higher than that following hospitalization (117 ± 55 mg vs 109 ± 57 mg; p = 0.014). Multivariate analysis identified younger age, higher systolic blood pressure, higher LVEF, prior use of renin-angiotensin system inhibitors, use of ivabradine, and a history of diabetes mellitus as independent factors for initiating a standard Sac/Val dose. Over a follow-up period of 18 months, incidences of cardiovascular death or first unplanned HF hospitalization were 18.69 and 33.11 per 100-person years for the TAROT-CHF and TAROT-AHF arms, respectively. Conclusion: The TAROT-HF study provided an opportunity to describe the clinical features of patients with HFrEF who received Sac/Val, assess the real-world utilization and efficacy of Sac/Val, and compare these patients with those included in prior registries.